Designing and Assessing Programs for Social Work - Tomczak, Stephen Monroe (Management and Leadership in Social Work: A Competency Based Approach, 2020)
The authors have had many years of leadership and management experience in a variety of settings and have discovered that there are few books that cover the majority of topics related to leadership and management specifically for social work education and practice. This book covers all the main areas of expertise required in a typical social work leadership and management experience. It incorporates all 21 competencies and 126 practice behaviors from the Network on Social Work Management (NSWM) and nine competencies and 29 practice behaviors espoused by the Council on Social Work Education (CSWE) and can serve as a textbook for social work programs at the graduate level. The book has many unique features. It provides a comprehensive list of leadership and management competencies from the NSWM and the CSWE along with a list of competencies and practice behaviors. The book presents leadership and management competencies and practice behaviors each chapter along with cases, examples, and activities of how to use them in practice situations. It discusses in detail the differences between management and leadership along with best management and leadership practices. The book provides examples of how to motive and successfully work with different age cohorts. It presents effective communication and marketing strategies. The book discusses in detail how to effectively work with groups and give examples of how to make meetings productive. It exhibits specific problem-solving and decision-making strategies along with examples. The book summarizes how to manage a range of organizational functions. It discusses the importance of collaborating with community groups and other stakeholders to succeed in making a difference. The book contains five parts that replicate the <abbrev>NSWM</abbrev>’s four domains of leadership: executive leadership in social work; resources management practices; strategic management and administrative skills for organizational growth and success; community collaboration; and supplemental materials.
Keywords: Leadership; Vocational qualifications; Social Work; dept.swk; faculty_collection; methods; Efficiency, Organizational; organization & administration; Leadership; Professional Competence; Personnel Management